The causal effects of education on wages: Evidence from Kyrgyzstan - (:unkn) unknown (UNIV ISLAM INDONESIA, 2019)
This study uses a Mincerian earnings function to estimate the effect of education and experience on the wages of women working in developed business and trade center of Bishkek, Kyrgyztan. It employs a robust median regression and M Regression to estimate the functions for both public and private sectors. The paper also estimates the function using a least squared regression for comparison. Findings/Originality: The results show that returns to education for women employees in the private sector are higher than that of in the public sector. In contrast, the returns to experience for women employees in the public sector are higher than those in the private sector. The study reveals that schooling has strong causal effects on wages. Therefore, the government should give sufficient priority to education. Every Som spent in quality education generates strong positive returns for the whole economy. So that Kyrgyz government should put more efforts to enable individuals staying longer in education.
Keywords: Returns to education; Wage distribution; Women employees in Bishkek; Mincer equation; econometric and statistical methods and methodology; QUANTILE REGRESSION; RETURNS; EARNINGS